Compton profiles and electronic structure of monoclinic zinc and cadmium tungstates. (December 2015) - Meena, B.S.; Heda, N.L.; Mund, H.S.; Ahuja, B.L.
Abstract: We report the first ever Compton scattering study of ZnWO4 and CdWO4 using 20 Ci 137 Cs Compton spectrometer at momentum resolution of 0.34 a.u. To compare the experimental Compton profiles, we have also deduced the momentum densities using density functional theory (DFT) within linear combination of atomic orbitals (LCAO) methods. It is seen that the experimental Compton profiles of both the tungstates give a better agreement with LCAO–DFT calculations within generalized gradient approximation (GGA) employing Perdew–Becke–Ernzerhof (PBE) exchange and correlation energies than other approximations included in the present work. Further, energy bands, density of states (DOS) and band gaps have also been calculated using LCAO–DFT–GGA–PBE scheme and full potential linearized augmented plane wave method. Both the computational schemes show a semiconducting nature of both the tungstates, with a direct band gap at Y point of Brillouin zone. Further, a relative nature of bonding on equal-valence-electron-density scale shows more covalent character in ZnWO4 than CdWO4 which reconciles with the conclusions drawn using integrated DOS and Mulliken's population data. Highlights: Presented first-ever Compton profile (CP) measurements on ZnWO4 and CdWO4 . Analyzed CP data in terms of first-ever LCAO–DFT calculations. Computed energy bands and DOS using LCAO and FP-LAPW schemes. Discussed DOS in terms of Mulliken's population. Interpreted bonding employing equal-valence-electron-density scale of CPs.